COMMUNICATION OF LECTURER IN DIGITAL ERA WITH ARSITOTELIAN RETHORICAL APPROACH - Riyanda Ilham Nuryadin; Indra Novianto Adibayu Pamungkas (ENSAINS JOURNAL, 2019)
Abstract:. The development of information and communication technology in the digital era has affected behaviors of society, including in the field of education. The development of information and communication technology, commonly referred as ICT (Information and Communication of Technology) it is currently increasingly encouraging efforts to adapt for using technology in teaching and learning process, with such conditions, making the lecturers / teachers are required to be able to use technology well without abandoning their communication skills as lecturers in learning process. This situation was also created due to the process of industrial revolution in various sectors of life so that transformed the world of education, including changing the process of forming and maintening relationships between lecturers and students. In this study, researchers will conduct this research to students of generation Z from the field of science-social science that generally covers the fields of communication, management, and applied science. Researchers conducted research on socio-science students because students from the scientific family had a tendency to use the right brain predominantly in their daily activities and researchers would also use the approach through a literature review of the Rhetorical Theory carried out by Aristotle and the use of Rhetoric on lecturers in digital era. By doing this research, researchers will try to change the communication process to lecturers to students of Z generation in the digital era.Keyword: Communication, Aristotelian Rethoric, Digital Era